Does local infiltration anesthesia on laparoscopic surgical wounds reduce postoperative pain? Randomized control study. (16th August 2018) - Sugihara, Mika; Miyake, Takahito; Miyagi, Yasunari; Oda, Takashi; Hazama, Yukiko; Sano, Rikiya; Nakamura, Takafumi; Shiota, Mitsuru; Shimoya, Koichiro
Abstract: Purpose: Recently, endoscopic surgeries are widely performed in the gynecological field. Several studies on the use of local anesthesia for pain control after laparoscopic surgery have been conducted; however, its effects remain controversial. Herein, a randomized control study on gynecological laparoscopic surgeries was conducted to analyze the effectiveness of local anesthesia on postoperative pain. Methods: Patients who underwent laparoscopic surgeries due to gynecologic benign diseases or endometrial cancer in the early stage were enrolled, and randomly divided into intervention (injected with levobupivacaine), and control (injected with saline) groups. The primary outcome was the dosage of analgesic consumption within 12 hours postoperatively. Results: A total of 147 patients were enrolled in the intervention group and 147 in the control group. The outcome of local anesthesia was not significantly different between the two groups during the whole analysis. We analyzed the effects of local anesthesia in the laparoscopic surgery subgroup. The dosage of analgesic consumption within 12 h after a laparoscopic hysterectomy (TLH) or TLH with pelvic lymph node dissection (TLH+PLD) in the intervention group was significantly smaller than that in the control group. Conclusion: Local infiltration anesthesia can effectively reduce postoperative pain in patients who underwent TLH or TLH +PLD.